2015
DOI: 10.1002/adv.21598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical, Thermal, and Morphological Behaviors of Polyurethane/Mahua Seed Cake Green Composite

Abstract: ABSTRACT:To know the possibility of using Indian butter tree seed waste (mahua seed cake [MSC]) as a filler in the production of value-added product such as polyurethane (PU) green composites, a series of PU composites have been fabricated with varying amounts, namely, 0, 2.5, 5.0, 7.5, and 10 wt%, of MSC, and their effects on the physicomechanical properties such as density, surface hardness, tensile strength, tensile modulus, and percentage elongation at break have been studied. It was found that the tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…2.2 Synthesis of PU/Algae biocomposites 50 ml of methyl iso butyl ketone (MIBK) solvent is placed in the necked round bottom ask. Calculated amounts of tolylene 2,4 disocyanates (TDI), castor oil (CO) and 3 drops of catalyst dibutyltin dilaurate (DLDBT) are added to MIBK solvent as per standard procedure (Madhukar, et al, 2015). The ask is then kept on digital hot plate tted with a condenser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.2 Synthesis of PU/Algae biocomposites 50 ml of methyl iso butyl ketone (MIBK) solvent is placed in the necked round bottom ask. Calculated amounts of tolylene 2,4 disocyanates (TDI), castor oil (CO) and 3 drops of catalyst dibutyltin dilaurate (DLDBT) are added to MIBK solvent as per standard procedure (Madhukar, et al, 2015). The ask is then kept on digital hot plate tted with a condenser.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental results are slightly higher than theoretical results. This is due to the aggregation of ller at a higher amount of the ller content and maybe the ller not wetted completely in the PU matrix (Madhukar, et al, 2015). The surface area of the uniform mass of specimens is decreases with an increase in the ller content.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…50 ml of methyl iso butyl ketone (MIBK) solvent is placed in the necked round bottom flask. Calculated amounts of tolylene 2,4 disocyanates (TDI), castor oil (CO) and 3 drops of catalyst dibutyltin dilaurate (DLDBT) are added to MIBK solvent as per standard procedure [6,7]. The flask is then kept on digital hot plate fitted with a condenser.…”
Section: Synthesis Of Pu/algae Biocompositesmentioning
confidence: 99%
“…Indian butter tree seed waste (mahua seed cake [MSC]) is sued as filler and a series of PU composites have been fabricated with varying amounts, namely, 0, 2.5, 5.0, 7.5, and 10 wt%, of MSC. It was found that the tensile strength of the green composites increased from 5.61 to 9.5 MPa and tensile modulus increased from 4.75 to 6.07 MPa with an increase in filler content from 2.5 to 7.5 wt% [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation